2014
DOI: 10.4088/jcp.14r09164
|View full text |Cite
|
Sign up to set email alerts
|

The US Food and Drug Administration’s Perspective on the New Antidepressant Vortioxetine

Abstract: Vortioxetine is a new treatment for MDD, and its adverse event profile is similar to that of other SSRIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
38
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 18 publications
8
38
0
1
Order By: Relevance
“…As the current success rate for psychiatric medications in Phase 3 RCTs hovers around 50%, the FDA concluded that the preponderance of the evidence supported the efficacy of vortioxetine 20 mg/day. [26,27] The results of the single longer-term, relapse-prevention study also were consistent with the FDA's appraisal of efficacy. [28] In this trial, a total of 693 depressed outpatients were treated for up to 12 weeks with 5-10 mg of vortioxetine, of which 396 responded and were then blindly randomized to continuation treatment or placebo.…”
Section: Phase 3 Studies and Fdasupporting
confidence: 65%
See 1 more Smart Citation
“…As the current success rate for psychiatric medications in Phase 3 RCTs hovers around 50%, the FDA concluded that the preponderance of the evidence supported the efficacy of vortioxetine 20 mg/day. [26,27] The results of the single longer-term, relapse-prevention study also were consistent with the FDA's appraisal of efficacy. [28] In this trial, a total of 693 depressed outpatients were treated for up to 12 weeks with 5-10 mg of vortioxetine, of which 396 responded and were then blindly randomized to continuation treatment or placebo.…”
Section: Phase 3 Studies and Fdasupporting
confidence: 65%
“…The US FDA review of this body of work is nicely summarized by Zhang and colleagues. [26] All of these studies enrolled adult outpatients with MDD (DSM-IV-TR criteria); one study focused specifically on patients age 65 and older. All studies required that patients were medically stable and were not taking concomitant medications that might complicate study treatment.…”
Section: Phase 3 Studies and Fdamentioning
confidence: 99%
“…There was a relatively low incidence of sexual dysfunction and sleep disruption [88,89]. Overall, vortioxetine showed strong evidence for antidepressant efficacy with good tolerability [90]. In addition, it showed improvement of cognitive dysfunction in patients with MDD.…”
Section: Vortioxetinementioning
confidence: 99%
“…Of course not-the observed differences in efficacy almost certainly pertain to problems with signal detection in contemporary RCTs of antidepressants, which, in the case of the studies of vortioxetine, was more evident in the United States than elsewhere in the world. This has not always been the case; as noted by Zhang et al, 1 the results of an earlier meta-analysis of regulatory submissions across several decades concluded that signal detection used to be better in studies conducted within the United States. 3 However, an opposite pattern was evident in the registration studies of vortioxetine, a point that was nicely illustrated by the findings of the study 4 conducted in late-life depression.…”
mentioning
confidence: 99%
“…1 It is almost certain, for example, that vortioxetine does not have a stronger antidepressant effect than the serotonin-norepinephrine reuptake inhibitors (SNRIs) duloxetine and venlafaxine. 1 However, Sanchez and colleagues 5 marshal evidence to suggest that the receptormediated effects of vortioxetine-which include antagonism of 5-HT 1D , 5-HT 3A , and 5-HT 7 receptors; partial agonism of 5-HT 1B receptors; and agonism of 5-HT 1A receptorsmay convey important differences in side effect profile (eg, fewer sexual side effects) and secondary therapeutic effects (eg, better effects on cognition) when compared to "purer" SSRIs such as escitalopram or the SNRI duloxetine. This difference in perspective is understandable, as the FDA uses a much higher standard to evaluate claims of superiority than is typical for people who are closely tied to a drug's development.…”
mentioning
confidence: 99%